Introduction to media production : the path to digital media production - Musburger, Robert B. 4 0 16; Kindem, Gorham Anders; 5 (Amsterdam ;;Boston : Elsevier/Focal Press, 2009)
A guide for creating digital media production from the creation of an idea, audience consideration, preproduction, production, postproduction, through distribution and exhibition.
Previous editions entered under Gorham Kindem.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Production and direction.;Production and direction.;Production and direction.;Production and direction. -- Motion pictures;Television;Analog electronic systems.;Digital electronics.;Motion pictures;Television;Analog electronic systems.;Digital electronics; 20; 2